(untitled) (World Bulletin of Education and Learning, 2025)
Animal metaphors serve as an essential linguistic and cultural phenomenon in the Uzbek language, reflecting unique worldviews, value systems, and social norms embedded in everyday communication. These metaphors, derived from the names and behavioral qualities of animals, are used to express human character, emotions, and relationships in a figurative manner. Their semantic structure is shaped by historical experiences, traditional beliefs, and culturally approved interpretations of animal traits. This study explores the semantic domains of animal metaphors commonly used in Uzbek speech and written discourse, investigates their figurative meanings, and analyzes the cultural attitudes they convey.